The Lost art of Tubal Ligation,Suture or Technique? - Viqar Ashraf; Rabia Sajjad (Pakistan Armed Forces Medical Journal, 2024)
Birth spacing is required to bring improvement in women’s quality of life. Contraception and birth spacing by the permanent method of female sterilization i. ebilateral tubal ligation, holds an important place in this regard. This case series deals with patients, reporting to Gynaecology Outpatient Department with surprise unexpected pregnancy /suspicion of pregnancy or secondary amenorrhea after permanent bilateral tubal ligation at time of last cesarean section. Basic objective was to identify the cause of failure of sterilization: Improper technique, wrong suture or wrong timing of procedure. Efforts were made to make proper technical recommendations for this procedure.